Antifungal susceptibility of Malassezia furfur, Malassezia sympodialis, and Malassezia globosa to azole drugs and amphotericin B evaluated using a broth microdilution method - Rojas, Florencia D (2014)
Fil: Rojas, Florencia D. Universidad Nacional del Nordeste. Instituto de Medicina Regional. Departamento de Micología; Chaco, Argentina.